Dispositivo intrauterino parcialmente migrado e incrustado en serosa de rectosigmoides tras 8 años de inserción - Bernuy Pérez, Sandra Lizzet (2015)
It is shown the clinical case of an intrauterine device partially migrated to the pelvic cavity and embedded in the serous rectosigmoid eight years after insertion. The diagnosis was made by transvaginal ultrasound and laparoscopy removal of the device by laparoscopy. Suture of rectum serous and uterus were performed. The patient had an uneventful postoperative course.